An Antibiotic Resistance Pattern and Microbial Agents Isolated from Raw Milk Samples from Acute and Sub-Acute Cases of Mastitis in Livestock - Majid Sadeghpour; Ehsan Estabraghi; Alireza Mokhtari; Sepideh Reihani (Tehran University of Medical Sciences, 2018)
Background and Aim: Milk is a suitable environment for most microorganisms. Pollution in the suckling production chain and its implementation result in unsatisfactory sanitation, long-term transportation, and the lack of facilities for storing milk. The purpose of the study was to identify and control the effects of common microorganisms of mast infections and their role in the transmission of diseases with milk as a major contribution to storage and, finally, the transmission of these pathogenic infections to humans. Materials and Methods: A total of 450 raw milk samples from traditional and industrial plants were collected around the city of Tehran. In order to determine the identity of the bacteria, their transmission to a differential culture, was used standard microbiological methods and antimicrobial susceptibility testing (Disc diffusion). Results: The results of biochemical experiments were conducted on 225 isolates from isolation and diagnosis of bacteria in raw milk, antibiotic susceptibility test in accordance with CLSI 2010 standard guidelines. Antibiotics of tylosin and streptomycin with the highest antibiotic resistance were 221 (98.2%) and 217 (96.5%), respectively, which were most susceptible to the tetra delta and ciprofloxacin respectively (0%, 100%) and 15 (6.7%) bacterial resistance cases were observed. Conclusion: According to the present situation and the results obtained, the level of contamination obtained from traditional and industrial livestock is still high.  Although regular mastitis and infections are commonly found by specialists, but the contamination caused by milking and collecting is higher than normal values. The frequent use of antibiotics and the resulting resistance has provided a very important and controversial problem.